Kinerja Keuangan Dan Penghematan Pajak Sebelum Dan Sesudah Revaluasi Aset - Agustina Felisia; Dian Purnama Sari (STIE Malangkucecwara, 2019)
Revaluation of assets is considered capable of fulfilling relevant information to investors and can improve the company's financial performance. In addition to improving financial performance, there are other studies that mention the revaluation of fixed assets may cause tax savings. Researches mostly discusse the impact of revaluation of fixed assets related to financial performance using quantitative methods, while researches looking at taxation aspects are discussed with qualitative methods. Therefore the researcher will try to connect financial performance using variables in the form of debt to equity ratio, operational profit margin, total turnover assets, and return on assets and tax savings using effective tax rate before and after revaluing fixed assets. The variable was tested using a mean difference test-MANOVA method and the sample used was a public company that revalued its fixed assets in 2013 year. The results of the study did not prove that there were differences in financial performance and tax savings before and after the company revaluing fixed assets. This has no effect because the company that revalues ​​fixed assets is merely to meet the target of the government or actually the impact of the tax changes does not have a significant influence because there may be other impacts such as new additional costs for example appraiser fees, increased depreciation costs, all of which may make the company’s profits declined and final tax must be paid by the company. Instead, the revaluation just increase the book value of fixed assets and not the fixed assets physically